Transcriptome and metabolome analyses provide insights into the relevance of pericarp thickness variations in Camellia drupifera and Camellia oleifera - Li, Yongjuan; Liao, Boyong; Wang, Yi; Luo, Huihua; Wang, Shimin; Li, Caiqin; Song, Wenpei; Zhang, Kunchang; Yang, Boqun; Lu, Shaoqiang; Zhang, Bipei; Li, Yongquan (Frontiers in Plant Science, 2022)
Camellia fruit is a woody edible oil source with a recalcitrant pericarp, which increases processing costs. However, the relevance of pericarp thickness variations in Camellia species remains unclear. Therefore, this study aimed to identify pericarp differences at the metabolic and transcription levels between thick-pericarp Camellia drupifera BG and thin-pericarp Camellia oleifera SG. Forty differentially accumulated metabolites were screened through non-targeted UHPLC-Q-TOF MS-based metabolite profiling. S-lignin was prominently upregulated in BG compared with SG, contributing to the thick pericarp of BG. KEGG enrichment and coexpression network analysis showed 29 differentially expressed genes associated with the lignin biosynthetic pathway, including 21 genes encoding catalysts and 8 encoding transcription factors. Nine upregulated genes encoding catalysts potentially led to S-lignin accumulation in BG pericarp, and transcription factors NAC and MYB were possibly involved in major transcriptional regulatory mechanisms. Conventional growth-related factors WRKYs and AP2/ERFs were positively associated while pathogenesis-related proteins MLP328 and NCS2 were negatively associated with S-lignin content. Thus, Camellia balances growth and defense possibly by altering lignin biosynthesis. The results of this study may guide the genetic modifications of C. drupifera to optimize its growth–defense balance and improve seed accessibility.